Virus-to-prokaryote ratio in the Salar de Huasco and different ecosystems of the Southern hemisphere and its relationship with physicochemical and biological parameters - Eissler, Yoanna; Castillo-Reyes, Alonso; Dorador, Cristina; Cornejo-D'Ottone, Marcela; Celis-Plá, Paula S. M.; Aguilar, Polette; Molina, Verónica (Frontiers in Microbiology, 2022)
The virus-to-prokaryote ratio (VPR) has been used in many ecosystems to study the relationship between viruses and their hosts. While high VPR values indicate a high rate of prokaryotes’ cell lysis, low values are interpreted as a decrease in or absence of viral activity. Salar de Huasco is a high-altitude wetland characterized by a rich microbial diversity associated with aquatic sites like springs, ponds, streams and a lagoon with variable physicochemical conditions. Samples from two ponds, Poza Rosada (PR) and Poza Verde (PV), were analyzed by epifluorescence microscopy to determine variability of viral and prokaryotic abundance and to calculate the VPR in a dry season. In addition, to put Salar de Huasco results into perspective, a compilation of research articles on viral and prokaryotic abundance, VPR, and metadata from various Southern hemisphere ecosystems was revised. The ecosystems were grouped into six categories: high-altitude wetlands, Pacific, Atlantic, Indian, and Southern Oceans and Antarctic lakes. Salar de Huasco ponds recorded similar VPR values (an average of 7.4 and 1.7 at PR and PV, respectively), ranging from 3.22 to 15.99 in PR. The VPR variability was associated with VA and chlorophyll a, when considering all data available for this ecosystem. In general, high-altitude wetlands recorded the highest VPR average (53.22 ± 95.09), followed by the Oceans, Southern (21.91 ± 25.72), Atlantic (19.57 ± 15,77) and Indian (13.43 ± 16.12), then Antarctic lakes (11.37 ± 15.82) and the Pacific Ocean (6.34 ± 3.79). Physicochemical variables, i.e., temperature, conductivity, nutrients (nitrate, ammonium, and phosphate) and chlorophyll a as a biological variable, were found to drive the VPR in the ecosystems analyzed. Thus, the viral activity in the Wetland followed similar trends of previous reports based on larger sets of metadata analyses. In total, this study highlights the importance of including viruses as a biological variable to study microbial temporal dynamics in wetlands considering their crucial role in the carbon budgets of these understudied ecosystems in the southern hemisphere.